Plasma Lp(a) Levels Are Increased in Patients with Chronic Thromboembolic Pulmonary Hypertension - Ignatescu, M.; Kostner, K.; Zorn, G.; Kneussl, M.; Maurer, G.; Lang, I. M.; Huber, K. (Thrombosis and Haemostasis, 1998)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a disease resulting from the thromboembolic obstruction of the segmental and/or large size pulmonary arteries, subsequently leading to pulmonary arterial hypertension. Incomplete resolution of acute pulmonary emboli and thrombus organization are believed to be important for the development of the disease. Primary pulmonary hypertension (PPH) is a further disease that at present is poorly understood but shows a clinical picture similar to CTEPH. Since lipoprotein(a) [Lp(a)], a genetically determined risk factor for atherosclerosis and thrombosis, has been found increased in plasma of patients with deep vein thrombosis and pulmonary embolism, we measured plasma Lp(a) levels in 40 patients with CTEPH and 50 patients with PPH and compared them to 50 matched controls. The median for Lp(a) plasma levels was significantly higher in CTEPH patients (26.6 mg/dl) than in PPH patients (9.6 mg/dl) and controls (7.2 mg/dl). Increased plasma Lp(a) could, therefore, play a significant role in the mechanisms of ongoing thrombosis and thrombus organization in CTEPH, while its possible role in PPH can be limited to a small number of patients.